Johannes Widmanns »Behende und hubsche Rechenung«. Die Textsorte >Rechenbuch< in der Frühen Neuzeit - Gärtner, Barbara (Reihe Germanistische Linguistik, 2000)
In the early modern age Rechenbücher (arithmetic books) were texts in German for an illiterate audience. A pragmatically oriented text analysis model is used to study these counting books, compare them with texts of different content and in other languages and locate them in the history of text varieties in German as an integral part of European cultural history. As a prototypic example of this text variety, the study contains a complete edition of the work by J. Widmann (approx. 1460/5 - after 1504) together with information on the author's life and works, on the place his book on arithmetic has in the history of mathematics, a brief commentary, an index of measurement units and a glossary.